Danil Hombergen OCSO, The Second Origenist Controversy. A New Perspective on Cyril of Scythopolis’ Monastic Biographies as Historical Sources for Sixth-Century Origenism, Studia Anselmiana 132, Roma 2001, ss. 448. - Szram, Mariusz (Vox Patrum, 2003)
review